The Management Of School Operational Assistance (A Site Study at Public Elementary School of Kramat 4 Magelang) - Sulasno , Sulasno (2012)
The objectives of this research are to describe (1) the planning of using School Operational Assistance at Public Elementary School of Kramat 4, Magelang. (2) The Budget of School Operational Assistance at Public Elementary School of Kramat 4, Magelang. (3) The reporting of School Operational Assistance at Public Elementary School of Kramat 4, Magelang. (4) The evaluation of School Operational Assistance at Public Elementary School of Kramat 4, Magelang. This research is a quantitative rearch and using ethnography design. This research is conducted at Public Elementary School of Kramat 4, Magelang. The main subject of the research is the principal, and BOS manager. The method of data collection use interview, observation, and documentation. Data analysis started from (1) data collection, (2) data reduction, (3) data display, and (4) conclusion. Data validity test uses credibility, transferability, confirmability, and dependability. The results of this research are (1) the planning of using of School Operational Assistance at public Elementary School of Kramat 4, Magelang is made by a special team formed by the principal with the school committee. The special team makes a priority of need that can be financed by the school operational assisstance fund includes textbooks, improvement of teachers' quality, school exams, consumables, service, teachers' salary, students activity, and grants for poor students. (2) the budget of school operational assistance at Public Elementary School of Kramat 4 Magelang adapts to the received fund and school program need. The received fund is not budgeted all, so the school is still have fund to the next need. (3) Reporting of school operational assistance at Public Elementary School of Kramat 4 Magelang prepared every month the latest on 15 th . The report contains all needs that financed with the School Opearational Assistance fund. (4) Evaluation of school operational assistance at Public Elementary School ofKramat 4 Magelang conducted through monitoring and accepting suggestion and criticism about School Operational Assistacne activities. The monitoring conducted routinethat is once a month and every three month by the principla, the head of Official Technical Implementation Unit that has been done every month, quarter Regional Officer Agency inspectorate, and also school committee and community. The evaluated aspects of School Operational Assistance include statistic of the recipient, distribution, absorbtion, and utilizing of the School Opearational Assistance fund.